PELAKSANAAN KOORDINASI ANTARA UNIT PERLINDUNGAN PEREMPUAN DAN ANAK POLRES PADANG PARIAMAN DENGAN LEMBAGA PERLINDUNGAN ANAK SUMATERA BARAT PADA TAHAP PENYIDIKAN TINDAK PIDANA ANAK - Prianto, Edi Karan; Rosadi, Otong (Program Magister Ilmu Hukum Universitas Ekasakti, 2019)
Investigation of criminal cases committed by children by police investigators inaccordance with Law Number 8 of 1981 concerning Criminal Procedure Law (KUHAP)and Law Number 11 of 2012 concerning the Child Criminal Justice System. The PariamanPolice PPA Unit handles at least 10 cases of child offenders who coordinate with the WestSumatra Child Protection Agency and P2TP2A Limpapeh Nan Gadang House, WestSumatra Province, so that the investigation process can proceed well. This research is adescriptive analytical study. The research results of the coordination of the PPA andP2TP2A Units in conducting investigations at the Padang Pariaman Regional Policebegan with the psychological assistance process of child offenders in the investigationprocess, medical assistance process, legal advocacy process in investigations, so that thechild investigation process was quickly carried out and in accordance with the ProtectionAct and the Child Criminal Justice System Act. Constraints encountered in thecoordination of the PPA and P2TP2A Unit in conducting investigations were theLimitations on the Number of Child Investigators Understanding Children's Investigations,the Limitations of the Number of West Sumatra LPA Members, the Limited Number ofP2TP2A Members, the Maximum Coordination between PPTP Units and P2TP2A in theInvestigation Process, and Child Factors / Family Actors who are less responsive in theinvestigation process. Addressing the obstacles encountered in the coordination of theProtection of Women and Children with the West Sumatra Child Protection Agency inconducting investigations at the Padang Pariaman Regional Police by means of trainingand cooperation with the West Sumatra Child Protection Agency and P2TP2A LimpapehNan Gadang House, West Sumatra Province, system cross subsidies between units,increased socialization related to the issue of child protection for the community, andmodernizing the juvenile justice system in accordance with community development.